Enzyme immobilization studied through molecular dynamic simulations - Bhattacharjee, Nicholus; Alonso-Cotchico, Lur; Lucas, Maria Fátima (Frontiers in Bioengineering and Biotechnology, 2023)
In recent years, simulations have been used to great advantage to understand the structural and dynamic aspects of distinct enzyme immobilization strategies, as experimental techniques have limitations in establishing their impact at the molecular level. In this review, we discuss how molecular dynamic simulations have been employed to characterize the surface phenomenon in the enzyme immobilization procedure, in an attempt to decipher its impact on the enzyme features, such as activity and stability. In particular, computational studies on the immobilization of enzymes using (i) nanoparticles, (ii) self-assembled monolayers, (iii) graphene and carbon nanotubes, and (iv) other surfaces are covered. Importantly, this thorough literature survey reveals that, while simulations have been primarily performed to rationalize the molecular aspects of the immobilization event, their use to predict adequate protocols that can control its impact on the enzyme properties is, up to date, mostly missing.